Mantle Cell Lymphoma Mimicking Rectal Carcinoma - Engin Kelkitli; Hilmi Atay; Levent Yıldız; Ahmet Bektaş; Mehmet Turgut (Case Reports in Hematology)
Mantle cell lymphoma (MCL) is a mature B-cell non-Hodgkin lymphoma. After the (11;14) translocation was identified as its constant finding in 1992, MCL was recognized as a separate subgroup of non-Hodgkin lymphoma (NHL). In MCL, extranodal involvement may be observed in the bone marrow, the spleen, the liver, and the gastrointestinal system (GIS). Cases of MCL that present with a massive and solitary rectal mass are rare in the literature. In this case report, our aim was to present an MCL patient with a rarely observed solitary rectal involvement mimicking rectal carcinoma and to discuss treatment options for this patient.